Neutralizing antibody responses to three XBB protein vaccines in older adults - Guo-Jian Yang; Mei Lu; Rui-Rui Chen; Shuang-Qing Wang; Sheng Wan; Xue-Dong Song; Guo-Ping Cao; Lei Lv; Xue-Juan He; Bing-Dong Zhan; Mai-Juan Ma (Signal Transduction and Targeted Therapy)
Abstract The ongoing COVID-19 pandemic has underscored the importance of strong immune defenses against emerging SARS-CoV-2 variants. While COVID-19 vaccines containing XBB subvariants have proven effective in neutralizing new SARS-CoV-2 variants, a gap remains in knowledge regarding neutralizing antibody responses in older adults aged >65 years against these newly emerged variants. This study was therefore undertaken to investigate and compare neutralizing antibody responses to three XBB-containing protein-based vaccines (trivalent XBB.1.5 vaccine, bivalent Omicron XBB vaccine, and tetravalent XBB.1 vaccine) head-to-head in 90 individuals aged >65 years. The results showed that all three XBB-containing vaccines substantially enhanced the neutralizing antibody response, with 100% of vaccinees having detectable antibody titers against ancestral D614G and variants BA.5, XBB.1.5, JN.1, KP.2, and KP.3 after booster immunization. Subsequent analysis indicated that the trivalent XBB.1.5 and tetravalent XBB.1 vaccines elicited higher levels of neutralizing antibodies compared to the bivalent Omicron XBB vaccine. The KP.2 and KP.3 variants displayed antibody resistance comparable to the JN.1 variant. Older adults produce similar neutralizing antibody responses to the vaccines regardless of their underlying medical conditions. These findings indicate that booster vaccination with XBB-containing vaccines can effectively elicit strong neutralizing responses against a number of SARS-CoV-2 variants in older adults over 65 years, which will help guide vaccine strategies in this elderly population.